The relationship between zinc deficiency and infectious complications in patients with hepatitis B virus-related acute-on-chronic liver failure. (11th November 2022) - Li, Xinhua; Wang, Lu; He, Na; Zhang, Yeqiong; Pang, Jiahui; Wang, Heping; Yu, Meng; Mei, Yongyu; Peng, Liang; Xu, Wenxiong
Abstract: Background: The prevalence of zinc deficiency is high in patients with chronic liver disease, but few studies have hitherto explored the relationship between the serum zinc level and hepatitis B virus (HBV)-related acute-on-chronic liver failure (ACLF). This study aimed to assess the association between zinc deficiency and infectious complications, and model for end-stage liver disease (MELD) score in patients with HBV-related ACLF. Methods: Patients with HBV-related ACLF from the Department of Infectious Diseases of the Third Affiliated Hospital of Sun Yat-sen University (Guangzhou, China) between January 2019 and December 2019 were retrospectively analysed in this study. Their demographic, clinical, and laboratory data were retrieved from the hospital information system and analysed. The Student's t -test was used for normally distributed continuous variables between two groups and the Chi-square test was used for categorical data. Univariate and multivariate logistic regression analyses were applied to identify independent parameters. Results: A total of 284 patients were included in this study, including 205 liver cirrhosis and 79 non-cirrhosis patients. The proportion of patients with zinc deficiency was the highest (84.5%), followed by subclinical zinc deficiency (14.1%) and normal zinc level (1.4%). Patients in the zinc deficiency group had a higher MELD score than the subclinical zinc deficiency or normal zinc group ( P  =   0.021). Age, total bilirubin, and serum zinc level were independent factors for infection ( Ps   <   0.05). The serum zinc level in patients without complications at admission was significantly higher than that in patients with complications ( P  =   0.004). Moreover, the serum zinc level in patients with prothrombin time activity (PTA) of <20% was significantly lower than that in patients with 20%   ≤   PTA   <   30% ( P  =   0.007) and that in patients with 30%   ≤   PTA   <   40% ( P  <   0.001). Conclusions: Zinc deficiency is common in patients with HBV-related ACLF. Zinc deficiency is closely associated with infectious complications and MELD score in patients with HBV-related ACLF.